COMMUNICATION STYLES ANALYSIS OF THE HOST ON EDUCATIONAL YOUTUBE CHANNEL FOR TODLER AND CHILDREN "KINDERFLIX" - Arina Muntazah,; Novalia,; Rindana Intan Emeilia,; Anggie Ayu Astria Latuperissa, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The rapid development of digital communication technology has encouraged the emergence of interactive learning media such as YouTube, which is increasingly used for early childhood education. One of the educational channels, Kinderflix, combines educational and entertainment elements (edutainment) through an expressive and engaging host. In this context, communication style plays a crucial role in delivering messages effectively to young audiences. This study aims to analyze the communication style of the host on the Kinderflix YouTube channel by applying Mead and Blumer’s Symbolic Interactionism theory and Norton’s communicator style framework. The research employs a descriptive qualitative method using purposively selected data from Kinderflix videos, verbal transcripts, and nonverbal observation notes based on educational relevance and interactivity. The findings reveal that the Kinderflix host applies three main communication styles: assertive, responsive, and attentive (child-centered). The assertive style is used to give clear directions, the responsive style builds emotional connection through empathy and praise, while the attentive style adapts language, tone, and gestures to children’s developmental characteristics. The synergy of these styles creates an interactive, engaging, and effective communication pattern that enhances understanding and learning motivation among early childhood audiences.